The Role of Green Economy in Promoting Sustainable Economic Growth in Indonesia - Lieansyah, Anggi; Putra , Adi; Haris, Abdul; Basri, Hasan (PT. Anagata Sembagi Education, 2024)
The green economy plays a crucial role in promoting sustainable economic growth by integrating environmental sustainability with economic development. This study examines the impact of green economy initiatives on Indonesia’s economic growth, highlighting key factors such as green investments, technological innovation, and government policies. Using a quantitative approach, this research analyzes data from various economic sectors to assess the effectiveness of green economic practices in driving sustainable development. The findings indicate that green investments and technological advancements significantly contribute to economic growth, while government policies serve as a crucial moderator in accelerating green economic transformation. However, several challenges remain, including high implementation costs, limited infrastructure, and a lack of public awareness regarding the long-term benefits of green practices. To overcome these challenges, collaboration between the government, private sector, and society is essential. Strengthening regulations, providing financial incentives, and increasing education on sustainability are key to enhancing Indonesia’s transition toward a greener economy. This study contributes to the growing literature on green economy implementation in developing countries and provides policy recommendations for improving sustainability-driven economic growth. Further research is needed to explore the long-term effects of green economic policies in specific industries and their comparative impact across different countries.